Validation of an instrument to assess the homecare competency of the family caregiver of a person with chronic disease - Gloria Mabel Carrillo; Beatriz Sánchez Herrera; Edier Mauricio Arias Rojas (Universidad de Antioquia, 2015)
Objective.This work sought to develop, validate, and determine the reliability of an instrument on Competency in Homecare of the family caregiver of an individual with chronic disease. Methodology. The test validation study was carried out in the following phases: 1) literature review; 2) analysis of results of programs to help family caregivers in Latin America; 3) exploration of the classification of nursing results (NOC) related to the family caregiver and discharge; 4) proposal of an instrument of care competence; and 5) psychometric tests: apparent validity with 25 family caregivers of individuals with chronic disease and six experts in the area; construct validity and reliability through internal consistency with 311 family caregivers of chronic patients. Results. The instrument on homecare competency of the family caregiver of an individual with chronic disease (CUIDAR, for the term in Spanish) has 60 items that inquire on six categories: knowledge, uniqueness, instrumentation, enjoyment of life, anticipation and relationships, and social interaction. The apparent validity evidences clarity, coherence, sufficiency, and relevance of the scale. With the factor analysis six components were obtained through the Varimax rotation in which most of the items are associated according to the categories proposed. The reliability (internal consistency) reported a Cronbach's alpha of 0.96. Conclusion. The Homecare Competency instrument permits assessing the capacity of a family caregiver to care for an individual with chronic disease, proving valid and reliable for the Colombian context.